(untitled) (Revista Innova Educación, 2026)
The study was conducted in a context marked by growing concern regarding the presence of academic misconduct in higher education, which affects both the quality of learning and the ethical training of students. Objective: To identify the level of knowledge and perception that university students have regarding academic misconduct. Methodology: A quantitative approach with a non-experimental, cross-sectional design and a descriptive-correlational scope. The sample consisted of 351 students from three universities in southern Peru, selected through non-probability convenience sampling. A questionnaire evaluating three dimensions was used: knowledge of dishonest practices, misconduct committed, and perception of the severity of such behaviors. Data analysis included the Kolmogorov-Smirnov test, Spearman’s correlation, and Pearson’s chi-square. Results: 70% of participants showed a high level of knowledge about misconduct; however, approximately 90% reported engaging in such practices with low frequency during the academic semester. Furthermore, 67.1% showed a high perception of severity toward these behaviors. A low-intensity positive correlation was identified between knowledge and perception (rho = 0.208; p = 0.0001), and a moderate-low positive correlation between motivational factors and the commission of misconduct. Conclusion: Despite an adequate level of knowledge and perception of severity, a discrepancy persists between knowledge and ethical action, influenced by academic and contextual factors, highlighting the need to strengthen institutional academic integrity policies.